CMOS Compatible Al‐Doped ZnO Sol–Gel Thin‐Film Properties. Issue 7 (29th January 2022) - Moussa, Nizar Ben; Lajnef, Mohamed; Jebari, Nessrine; Mahut, Frédéric; Villebasse, Cédric; Lafosse, Xavier; David, Christophe; Chaste, Julien; Chtourou, Radhouane; Herth, Etienne
Abstract : Zinc oxide (ZnO) is a low‐cost class of n‐type inorganic semiconductors with a large exciton binding energy (≈60 meV), wide direct bandgap (3.37 eV), and the most important material for various fields of industrial and deep‐tech applications. Herein, a complementary metal–oxide–semiconductor (CMOS) temperature compatible (400 °C)‐ integrated circuit (IC) process based on the sol–gel method is described. The properties of aluminum (Al)‐doped ZnO (AZO) thin films were investigated. The Al content, Al/(Al+Zn) ratio, varies from 0 to 10% and exhibits compressive stresses from −4 to −1.8 GPa. At low dopant concentrations, the Al content acts as an electrical dopant, while at higher dopant concentrations, it acts as an impurity. The electrical resistivity, which was only 3 × 10 −3 Ω cm, is inversely related to the orientation of the thin film, which was preferably along the (0 0 2) direction. The optical bandgap energy of AZO thin films was determined to be in the range of 3.34–3.87 eV. Herein, a novel method to change the Al content of doped AZO thin films to improve their properties is described, which is suitable for next‐generation flexible, microsystem, and optoelectronic devices. Abstract : New possibilities for doped and undoped ZnO thin films based on the sol–gel route is opened up in this work. The importance of the aluminum (Al) content for the direct band gap of the group ZnO semiconductor II–VI is emphasized. Finally, the possibility that Al‐doped ZnO thin films can be useful for a wide range of applications is highlighted.